Business strategy for market development of photography and videography business in pt. Delapan pilar karya - Nugraha, Rendika; Fachira, Ira (The Indonesian Journal of Business Administration, 2016)
Abstract - PT. Delapan Pilar Karya is a company that established in August 2014 and focusing the business in photography and videography with brand name Eight Motion. Current situation of Eight Motion is the revenue rely from business market segment, which has long payment term and occasional project that impact to instability of sales performance. Author conducts external analysis with some tools such as PEST and Porter five forces to examine what kind of external opportunities for market development that can be captured to earn stable revenue. Internal analysis with some tools such as STP, Marketing Mix 7P, Resource based view, VRIO, and business model canvas also conducted to examine current internal situation of Eight Motion.Â  SWOT analysis utilized to summarize external and internal analysis. In strategy formulation, author utilized EFAS and IFAS table in order to examine and quantify the strategic factors from SWOT analysis. TOWS matrix developed in order to create alternative strategies. Porter generic strategies utilized by the author to determine which business direction should be through. Diamond Strategy utilized in order to deliberate how the strategy formulation will works by explaining five elements of strategy from arenas, vehicle, differentiators, staging, and economic logic. Finally, author utilized business model canvas in order to capture business activity overview as the implication of strategy formulation. Activity plan that incorporates marketing, Product and operation strategy created in order to become guideline of strategy execution.Â Keywords: Photography and Videography Business, Market Development, Diamond Strategy